Views of Iranian prison staff towards needle-exchange program in prison - Shahbazi, Mohammad; Moazen, Babak (Drugs, 2016)
Aims: Prison staff members have a core role in the provision of harm reduction strategies in prison. This study aimed to evaluate the attitudes of prison directors, managers and health staff toward Needle Exchange Program (NEP) among people who inject drugs in Iranian prisons. Methods: With a grounded theory design, this qualitative study was conducted in 2011 in Iran. The study population included directors of provincial prison organisations, prison managers, heads of health departments in prisons, prison health officers, physicians, counsellors and healthcare workers in prisons. Participants’ responses were collected via focus group discussions. Results: Attitudes of the participants could generally be categorised in three including: Health-related aspects; Behavioural and social aspects; and Legal, organisational and financial aspects. Those who were in line with the existence of NEP in prisons mentioned some pre-requisites for supporting this program in prisons. Conclusion: Positive and negative views of Iranian prison staff toward NEP in prisons suggest that there are many obstacles to the provision of harm reduction strategies in prison. Consideration of socio-cultural parameters of the target community as well as combination of NEP and other harm reduction strategies might help to improve the effectiveness of harm reduction in prisons.